Pengaruh Penggunaan Alat Permainan Edukatif (APE) sebagai Media Pembelajaran Tematik terhadap Hasil Belajar Siswa Kelas I di SDIT IQRA’ 2 Kota Bengkulu - Gustari, Nopian (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to determine the effect of the use of Educative Game Tools media on student learning outcomes in the Thematic subject of class 1 flat shapes at SDIT IQRA' 2 Bengkulu City. This type of research is a quantitative approach. The population in this study were all first-grade students, while the sample in this study were students in grades 1A and 1B at SDIT IQRA' 2 Bengkulu City, with 26 students in each class. The sampling technique used was purposive sampling technique. Data collection techniques are observation, tests and documentation. Testing the hypothesis in this study using the t test formula. The results of this study are that there is an effect of using Educative Game Tools on student learning outcomes in the Thematic subject of flat shape material at SDIT IQRA' 2 Bengkulu City between the control class and the experimental class. This is evidenced from the results of the calculation of the t-test test data for learning outcomes using the Independent Sample T-Test obtained t-count = 3.812 and t-table = 1.711. The significance value in the Sig table. (2 tailed) obtained 0.000 ≤ 0.05 then Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence on student learning outcomes in the thematic subjects of class flat material at SDIT IQRA' 2 Bengkulu City.